Proteomic analysis of isogenic rice lines under brown planthopper infestation - Pathichindachote, Wanwarang; Panyawut, Natjaree; Sikaewtung, Kannika; Chakhonkaen, Sriprapai; Kittisenachai, Suthathi; Yingchutrakul, Yodying; Jamboonsri, Watchareewan; Kamolsukyunyong, Wintai; Roytrakul, Sittiruk; Patarapuwadol, Sujin; Muangprom, Amorntip (วารสารแก่นเกษตร, 2021)
The brown planthopper (BPH) is a major rice pest in Thailand. In this study, comparative proteomic analysis was applied to investigate total protein expression of rice plants under BPH infestation. Proteomic profiles of 2 contrasts BC3F5 isogenic lines including BIL15 (resistant-harboring QTL from Chr6), and BIL7 (susceptible-without any QTL) derived from Rathu Heenati (RH, BPH-resistant-donor) and KDML105 (Thai Jasmine rice-BPH-susceptible-recipient) were compared. The total expressed proteins were extracted from all the above ground portion of 25 day-old seeding, with and without BPH infestation at 3 and 24 hours after infestation (HAI). Proteomic analysis could define some interested candidate BPH responsive proteins specifically expressed in the resistant rice line (PSER). For early response investigation, the PSER under BPH treatment at 3 hours after infestation (PSER3) were focused and identified some interesting proteins such as wall-associated receptor kinase 2 (WAK2), serine/threonine-protein kinase OXI1 (OXI1) and TPR domain containing protein. WAK2 could perceive free calcium ion or pectin leaked from wounding cell wall following transfer signaling to MAPK cascade by its kinase activity. OXI1 contained kinase activity might play a role in MAPK signaling pathway. TPR domain containing protein could facilitate BPH defense through wax production which perturb insect-plant physical interaction. In conclusion, the identified PSER3 might initiate plant immune system through MAPK cascades. MAPK signaling might regulate expression of some defense related-functional proteins and related-transcription factors. The information obtained could further contribute for selecting potential candidate genes to develop effective functional markers. The potential resistance genes could facilitate for BPH resistant rice improvement using marker-assisted selection or genetic engineering.